Amine-Functionalized Silver Nanoparticles: A Potential Antiviral-Coating Material with Trap and Kill Efficiency to Combat Viral Dissemination (COVID-19) - Tiwari A.K.; Gupta M.K.; Pandey G.; Pandey S.; Pandey P.C. (My University, 2025)
The outbreak of COVID-19 has drastically affected the daily lifestyles of people globally where specific Coronavirus-2 transmits primarily by respiratory droplets. Structurally, the SARS-CoV-2 virus is made up of four types of proteins in which S-protein is indispensable among them, as it causes rapid replication in the host body. Therefore, the glycine and alanine composed of HR1 of S-protein is the ideal target for antiviral action. Different forms of surface-active PPEs can efficiently prevent this transmission in this circumstance. However, the virus can survive on the conventional PPEs for a long time. Hence, the nanotechnological approaches based on engineered nanomaterials coating on medical equipments can potentially prevent the dissemination of infections in public. Silver nanoparticles with tuneable physicochemical properties and versatile chemical functionalization provide an excellent platform to combat the disease. The coating of amine-functionalized silver nanoparticle (especially amine linked to aliphatic chain and trialkoxysilane) in its nanostructured form enables cloths trap and kill efficient. PPEs are a primary and reliable preventive measure, although they are not 100% effective against viral infections. So, developing and commercializing surface-active PPEs with trap and kill efficacy is highly needed to cope with current and future viral infections. This review article discusses the COVID-19 morphology, antiviral mechanism of Ag-NPs against SARS-CoV-2 virus, surface factors that influence viral persistence on fomites, the necessity of antiviral PPEs, and the potential application of amine-functionalized silver nanoparticles as a coating material for the development of trap and kill-efficient face masks and PPE kits. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC 2022. Springer Nature or its licensor holds exclusive rights to this article under a publishing agreement with the author(s) or other rightsholder(s); author self-archiving of the accepted manuscript version of this article is solely governed by the terms of such publishing agreement and applicable law.